The knowledge and self-management educational needs of older adults with knee osteoarthritis: a qualitative study - Kamsan, Siti Salwana; Ajit Singh, Devinder Kaur; Tan, Maw Pin; Kumar, Saravana (Public Library of Science, 2020)
Knee osteoarthritis (KOA) is closely related with ageing, physical disability and functional dependency. The course of KOA is considered progressive and irreversible. Engagement with self-management may, however, minimize the impact of KOA. To be fully engaged with self-management activities, knowledge about KOA is a prerequisite. There is limited empirical data on older adults’ understanding on KOA and their information needs about KOA. Therefore, the aims of this study were to explore older adults’ knowledge about KOA and their perspectives on the information required to enable self-management. Three focus groups were conducted with 16 older adults with KOA. The sample consisted of three men and thirteen women with the mean age 73.2 years (range from 61 to 89). Thematic content analysis revealed two themes which were understanding about KOA and information needed about KOA. Participants’ knowledge about KOA varied between individuals with many expressing that they needed more information about KOA. A targeted strategy is needed to educate older adults about KOA in order to support and prepare them for self-management.